The evolution of eccentric training as treatment for patellar tendinopathy (jumper`s knee): a critical review of exercise programmes - Visnes, H.; Bahr, R. (British Journal of Sports Medicine, 2007)
Background and aim: Eccentric training has become a popular treatment for patellar tendinopathy. Our purpose was to review the evolution of eccentric strength training programmes for patellar tendinopathy with a focus on the exercise prescriptions used, to help clinicians make appropriate choices and identify areas needing further research.